The coral assemblages of an off‐shore deep Mediterranean rocky bank (NW Sicily, Italy). (2nd August 2013) - Bo, Marzia; Cerrano, Carlo; Canese, Simonepietro; Salvati, Eva; Angiolillo, Michela; Santangelo, Giovanni; Bavestrello, Giorgio
Abstract In this study we characterized the deep assemblages dwelling at 200–250 m depth on a large shoal off Capo St. Vito Promontory (Northwestern coast of Sicily, South Tyrrhenian Sea) by means of ROV‐imaging. Two assemblages of suspension feeders, dominated by the gorgonian Callogorgia verticillata and by the black coral Leiopathes glaberrima, together with a tanatocoenosis of the colonial yellow scleractinian coral Dendrophyllia cornigera, were examined. The three main species were significatively distributed into two areas corresponding to different habitat preferences: a more elevated hardground hosting black corals and a gently sloping, silted rocky bottom hosting the other coral species. The study area is subjected to a heavy pressure from the professional fishery, resulting in the mechanical damage of numerous colonies, some of which are then overgrown by various epibionts including a parasitic bioluminescent zoanthid, new for the Mediterranean fauna, and tentatively identified as Isozoanthus primoidus. In the Mediterranean Sea, these deep off‐shore rocky banks are widely known among recreational and professional fishermen due to their rich fish fauna. However, there has been still little effort into quantifying and characterizing the extent of the impact and its consequences on the benthic communities, which may represent, as in this case, only a partial picture of their original structure and extent.